What is classical liberal history? - Douma, Michael J.; Magness, Phillip W. (Lexington Books, 2017)
This collection examines the classical liberal perspective within the professional study of history. The contributors investigate the origins and development of the classical liberal approach, argue for its revival within academia, and analyze its relevance to such topics as economics, civil liberties, feminism, and civil rights.